The principle of population vs. the Malthusian trap: A classical retrospective and resuscitation - Tim Lüger (Technische Universität Darmstadt, Department of Law and Economics, 2018)
In spite of two centuries of extensive debate, a consistent framework of the classical theory of population on which economists can universally agree has not been established. This means that either the theory lacks consistency or it has been misunderstood in important ways. This paper attempts to settle this issue by arguing that the latter was the case, revealing prevailing misconceptions. Since a large amount of these misconceptions most probably arose from the lack of a consistent nomenclature, the paper intends to clarify the classical theory of population by employing unambiguous definitions of the principle of population, the Malthusian trap, positive checks and preventive checks to population. The classical theory of population can then be applied to analyze the transition from economic stagnation to economic growth. As a result, numerous current theories trying to explain the transition to growth that are based on an increase of production will prove secondary when compared to the great preventive check.
urn:nbn:de:tuda-tuprints-73419
Keywords: B12; J1; N3; O11; 330; Demographic Transition; Malthusian Trap; Unified Growth Theory; Classical Growth Theory; Positive Checks; Preventive Checks